2022
DOI: 10.1021/jacs.2c00119
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Exosomes for Subtype-Based Diagnosis of Breast Cancer

Abstract: Breast cancer is very heterogeneous and the most frequently diagnosed cancer worldwide, and precise therapy targeting specific subtypes may improve the survival rates of breast cancer patients. In this study, we designed a biomimetic vesicle by camouflaging catalytic DNA machinery with a breast cancer cell membrane, which enabled the molecular classification of circulating exosomes for subtype-based diagnosis through homotypic recognition. In addition, the vesicles specifically targeted and fused with breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 49 publications
0
56
0
Order By: Relevance
“…In addition to genetic engineering membranes, vesicles made from exosome-derived cell membranes were used according to the same phenotypic features. Cao et al designed a homotypic recognition method to detect exo-miRNAs based on catalytic DNA machinery enveloped by biomimetic vesicles which fuse with cancer exosomes ( Figure 6 A) [ 85 ]. In this method, two hairpin probes, electroactive MB-labeled H1 and N3-labeled H2 are camouflaged by specific biomimetic vesicles which are immobilized on anti-CD44@IMBs.…”
Section: In Situ Detection Of Exo-mirnamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to genetic engineering membranes, vesicles made from exosome-derived cell membranes were used according to the same phenotypic features. Cao et al designed a homotypic recognition method to detect exo-miRNAs based on catalytic DNA machinery enveloped by biomimetic vesicles which fuse with cancer exosomes ( Figure 6 A) [ 85 ]. In this method, two hairpin probes, electroactive MB-labeled H1 and N3-labeled H2 are camouflaged by specific biomimetic vesicles which are immobilized on anti-CD44@IMBs.…”
Section: In Situ Detection Of Exo-mirnamentioning
confidence: 99%
“…Ramshani et al identified the overexpression of miR-21 from liver cancer patients [ 73 ]. In contrast to clinical testing attempts that look solely at miRNA concentrations, the method Cao et al developed can distinguish between phenotypes [ 85 ]. The ER-positive luminal subtype of breast cancer patients was analyzed with good discrimination.…”
Section: Exo-mirna Biosensing For Liquid Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the analysis is susceptible to interference of free miRNAs in biofluids, whose abundance is several orders higher than exosomal miRNAs [22][23][24] . Alternative to the sequence amplification-based strategies, a series of in-situ exosomal miRNAs bioassays have been recently developed by directly or indirectly importing DNA probes into membrane vesicles, such as gold nanoflares (Au NFs) and molecular beacons (MBs) [25][26][27] . Zhou et al designed a virus-mimicking fusogenic vesicle-encapsulated MBs probe, which can rapidly detect extracellular vesicle miRNAs within 2 h via membrane fusion 28 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, TNBC is usually diagnosed by imaging examinations and tissue biopsy, which cannot achieve early diagnosis, are invasive and associated with the risk of arousing tumor spreading [ 5 , 6 ]. Liquid biopsy based on tumor markers is an emerging technique with the advantages of non-invasive, simple operation, low cost and high throughput in analysis.…”
Section: Introductionmentioning
confidence: 99%